Joint Impact Assessment of CTA's support to IPACC (2003-2013) - Thaw, Davine; Crawhall, Nigel (Technical Centre for Agricultural and Rural Cooperation, 2020)
This report is the result of the joint impact study of CTA support to ACP partner organisations and networks led by the CTA in Wageningen, which details the impact of the relationship and collaboration between IPACC and CTA over 7 years beginning from 2007. It follows the early stages of this study, which included the Powerpoint and the quick scan and provides an in-depth look at, not a chosen aspect of the quick scan, but what IPACC learned while doing the quick scan.